Family business and performance: the power of women - Paiva, I.; Carvalho, L. (International Conference of Gender Research, 2018)
The impact of gender specificities on family businesses and performance remains an understudied area. Previous literature highlights the passive and distant role of women in family businesses, but also suggests that women start to intervene in management when corporate performance begins to deteriorate. Some earlier studies draw attention to women’s role and influence in succession issues and the development of companies. The purpose of this research is to explore the role of women in the management of corporate performance through the case study of Casa Ermelinda Freitas, a Portuguese family firm in the wine sector. Since it was established over 90 years ago, it has always been managed by women. It is currently managed by the fourth generation of women and they are committed to promoting their own brand and the growth of the company. The case aims to answer the following research question: How does management by women influence corporate performance in a traditional family business? This case study adopts a qualitative methodology based on documental analysis of financial reporting statements and information collected from the company website and media. The study contributes to the under-researched topic of corporate performance by women in family businesses using financial reporting analysis, notably in the wine sector, which is traditionally managed by men.